The tall man [videorecording (DVD)] - Biel, Jessica, 1982-; Ferland, Jodelle, 1994-; McHattie, Stephen; Davis, William B., 1938-; Ferris, Samantha, 1968-; Wheeler, Colleen, 1967-; Sanford, Garwin; Miserez, Clément; Laugier, Pascal, 1971-; Laugier, Pascal, 1971- (Image Entertainment, 2012)
When her child goes missing, a mother looks to unravel the legend of the Tall Man, an entity who allegedly abducts children.